Experimental and computational approaches to reveal the potential of Ficus deltoidea leaves extract as α-amylase inhibitor - Abu Bakar, Amirul Ridzuan; Manaharan, Thamilvaani; Merican, Amir Feisal; Mohamad, Saharuddin (Taylor & Francis, 2018)
Ficus deltoidea leaves extract are known to have good therapeutic properties such as antioxidant, anti-inflammatory and anti-diabetic. We showed that 50% ethanol-water extract of F. deltoidea leaves and its pungent compounds vitexin and isovitexin exhibited significant (p < 0.05) α-amylase inhibition with IC50 (vitexin: 4.6 μM [0.02 μg/mL]; isovitexin: 0.06 μg/mL [13.8 μM] and DPPH scavenging with IC50 (vitexin: 92.5 μM [0.4 μg/mL]; isovitexin: 0.5 μg/mL [115.4 μM]). Additionally, molecular docking analysis confirmed that vitexin has a higher binding affinity (-7.54 kcal/mol) towards α-amylase compared to isovitexin (−5.61 kcal/mol). On the other hand, the molecular dynamics findings showed that vitexin-α-amylase complex is more stable during the simulation of 20 ns when compared to the isovitexin-α-amylase complex. Our results suggest that vitexin is more potent and stable against α-amylase enzyme, thus it could develop as a therapeutic drug for the treatment of diabetes.